Back to the drawing board: exploring drawing as a path to expand creativity and imagination - Dalke, Madison (Kansas State University, 2019)
Environmental design is a field that relies on imagination and creativity to produce ideas for creating places. Designers must actively develop their imagination and creativity to design for the increasing complexity of the world (Runco 2004). One activity that expands these elements is drawing. Drawing encourages abstract thought and increases the connections in the brain’s neural network (Tallinen et al. 2014). Because of these aspects drawing has the potential to expand the mind's eye. This study attempts to answer the research question "How does the act of drawing as art affect a designer’s creativity during the environmental design process?" To answer this question, an experimental design using a creativity test was used to study the influence of drawing on creativity. The study was conducted using participants from Kansas State University Environmental Design program. In the study, the control group (N=35) takes the creativity test, and the intervention group (N=35) completes a drawing booklet before taking the test. The results were analyzed quantitatively and qualitatively to examine differences in the level of creativity. The study concluded drawing as art increased an individual’s originality and elaboration of design. Subjects in the intervention group were able to produce more unique and detailed designs than those in the control group. Overall even adding a short ten-minute drawing exercise to the design process does increase creativity. The study shows that designers can foster their own creativity through the simple process of drawing as art.
Keywords: Landscape architecture; Drawing; Creativity; Imagination; Design process; Environmental design